2015
DOI: 10.1007/s10096-015-2349-2
|View full text |Cite
|
Sign up to set email alerts
|

Direct susceptibility testing by disk diffusion on clinical samples: a rapid and accurate tool for antibiotic stewardship

Abstract: We compared the accuracy of direct susceptibility testing (DST) with conventional antimicrobial susceptibility testing (AST), both using disk diffusion, on clinical samples. A total of 123 clinical samples (respiratory tract samples, urine, vaginal and abdominal abscess discharges, bile fluid and a haematoma punctate) were selected on various indications; direct inoculation on Mueller–Hinton agar and antibiotic paper disks were applied. In parallel, standard culture, identification and AST on the colonies grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 23 publications
6
35
1
2
Order By: Relevance
“…A significant correlation has been reported previously for disk diffusion and BMD assays for many species/drug combinations (e.g. Berghaus et al, 2014;Coorevits et al, 2015;Matar et al, 2003).…”
Section: Correlation Between Disk Diffusion and Broth Microdilution Asupporting
confidence: 68%
“…A significant correlation has been reported previously for disk diffusion and BMD assays for many species/drug combinations (e.g. Berghaus et al, 2014;Coorevits et al, 2015;Matar et al, 2003).…”
Section: Correlation Between Disk Diffusion and Broth Microdilution Asupporting
confidence: 68%
“…The main criticism of such direct susceptibility test (DST) is the non-standardized sample and mixed cultures, which may lead to inaccurate results 22 , 23 . Nevertheless, numerous studies conducted over the past two decades indicate the applicability of DST in the diagnosis of infections 24 27 .…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Rosa et al concluded that Sysmex UF-5000 showed high diagnostic accuracy in UTI screening with a low rate of false negatives, and that the instrument can predict Gram negative bacteria with a high sensitivity and in high agreement with culture [8]. Direct AST on urine has been evaluated in previous studies [20][21][22][23][24] with promising results. Recently, Wei et al recently suggested the combination of flow cytometry (UF 1000), MALDI-TOF, MS, and VITEK 2 provided a direct, rapid, and reliable identification and AST method for assessing urine samples, especially for Gram negative bacterial infections [25].…”
Section: Direct Antibiotic Susceptibility Testingmentioning
confidence: 99%